Analysis of Islamic Education Books and Character in Psychological Perspective Children Development - Mas ruroh (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
This research was conducted because of the background of the problems thatSeeing the existing phenomena, there are books in which contain content that is not in accordance with the developmental psychology of students.Textbooks on Islamic religious education and manners for the first grade elementary school 2013 curriculum which have technical differences with the previous curriculum, one of which is textbooks prepared and made by the Minister of Education and Culture.The problem formulations of this thesis is First, what is the appropriateness of the material / content in the first grade Islamic Education and Characteristics textbook in the 2013 curriculum in terms of the psychology of cognitive and language development, socio-emotional development and social development. Second, how is the feasibility of presenting Islamic Religious Education textbooks and the first grade character in the 2013 curriculum in terms of cognitive and language development psychology, socio-emotional development and social development.Third, the elementary school 2013 curriculum is reviewed from the psychology of cognitive and language development, socio-emotional and social development.This type of research is a library research (research) using descriptive-qualitative research methods. The results of the study indicate that the feasibility of the content / material in terms of completeness of the material and the breadth of the material is generally appropriate, but in several chapters of the lesson there are basic competencies and indicators that are not suitable. The feasibility of the presentation is in accordance with the developmental psychology of the students concerned, as well as the appropriate language feasibility, using general and clear vocabulary so that it is easy to understand.